Security management of radioactive material in use and storage and of associated facilities : technical guidance (IAEA nuclear security series ;, 2022)
"Security management for radioactive material in use, storage and associated facilities includes the establishment and implementation of policies, plans, procedures and processes for the security of radioactive material. Security management assists to ensure that the security systems are effective, reliably operated and maintained with the necessary resources. Based on extensive input from technical and legal experts, this publication sets forth security management as an essential tool to verify that personnel, procedures and equipment operate interdependently and in an integrated manner, and that the leadership and personnel responsible for security demonstrate the highest commitment towards promoting a robust nuclear security culture within the organization. This Technical Guidance references and takes into account other IAEA Nuclear Security Series publications that provide guidance relating to security management. The document further provides guidance , including on the development of a security plan for radioactive material in use and in storage and for associated facilities. The Security Plan is an essential component of an operators licensing submission package. This Technical Guidance takes into account other IAEA Nuclear Security Series publications that provide guidance relating to security management and relating to security plans."--Publisher's description.